The EFFORTS TO IMPROVE MORAL DEVELOPMENT OF 5-6 YEAR OLD CHILDREN THROUGH AUDIO VISUAL MEDIA AT TK AL-HABIB KABUPATEN SERDANG BEDAGAI - Ni Komang Nandhita Dharma Santy; Muhammad Basri; Idris Siregar (Cakrawala Pedagogik, 2024)
This study aims to determine the improvement of moral development of children aged 5-6 years through audio-visual media at Al-Habib Kindergarten, Serdang Bedagai Regency. The formulation of the problem in this study are: 1) How is the moral development of children aged 5-6 years before using audio-visual media at Al-Habib Kindergarten? 2) How is the learning process using audio-visual media in improving the moral development of children aged 5-6 years at Al-Habib Kindergarten? 3) How is the moral development of children aged 5-6 years after using audio-visual media at Al-Habib Kindergarten? This type of research is classroom action research (CAR) with the subjects of the study being children aged 5-6 years in class A consisting of 20 children and the object of this research is the improvement of children's moral development. Data collection techniques in this study were carried out through observation and documentation. Data analysis techniques used percentage analysis. The results of the study conducted at Al-Habib Kindergarten, Serdang Bedagai Regency showed that the moral development of children aged 5-6 years can be improved through audio-visual media. The results can be seen from the results of observations in the Pre-Cycle, the average value obtained was 34.63%, while the results of observations in Cycle I, the average value obtained was 50.71%, so that there was an increase of 16.08%, and the results of observations in Cycle II showed that children's moral development increased with an average value of 78.56%, so that from Cycle I to Cycle II, children's moral development increased by 27.85%, while from Pre-Cycle to Cycle II, it increased by 43.93%.